2015
DOI: 10.14569/ijarai.2015.041005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Text Reading System for Digital Open Universities

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Vector control using medicinal plants has longtime demonstrated its effectiveness on the developmental stages of mosquitoes [30,31]. However, several studies have shown that the combination of natural molecules would better overcome the increasing resistance mechanisms developed by mosquitoes rather than with isolated compounds [32].…”
Section: Discussionmentioning
confidence: 99%
“…Vector control using medicinal plants has longtime demonstrated its effectiveness on the developmental stages of mosquitoes [30,31]. However, several studies have shown that the combination of natural molecules would better overcome the increasing resistance mechanisms developed by mosquitoes rather than with isolated compounds [32].…”
Section: Discussionmentioning
confidence: 99%